VEHICLE ROUTING PROBLEM ON JUICE DISTRIBUTION USING NEAREST NEIGHBOR METHOD - Tamyiz, Muchammad; Waluyo Prasetyo (2477 - 6165, 2018)
Product distribution problem becomes an important topic in a company transportation system. PT Amanah Prima Indonesia (API), a company that focuses on national-scalejuice production. With the sum of scattered consumers in Semarang, it is necessary a solution in the products distribution to obtain operational efficiency.The method used is Nearest Neighborh Algorithm. The results obtained are: (a) The total distance traveled by the truck results in a distance savings of 144.20 Km or 40.06%, (b) The time of product distribution can be reduced for 5.15 hours or by 30.31%, (c) The savings of fuel cost resulted Rp.108,150,- or 40.06%, (, d) There is no difference cost for the driver and partner, which is Rp.600,000, and (e) Total savings for product distribution cost obtained of Rp.108,150, - or 12.43%. Keywords: Cost, VRP, Transportation.